Impact of waves on phytoplankton activity on the Northwest European Shelf: insights from observations and km-scale coupled models - Dale Partridge; Ségolène Berthou; Rebecca Millington; James R. Clark; Lucy Bricheno; Juan Manuel Castillo; Julia Rulent; Huw Lewis (Ocean Science, 2026)
The spring bloom is an annual event in temperate regions of the North Atlantic Ocean where the abundance of photosynthetic plankton increases dramatically. The timing and intensity of the spring bloom is dependent on underlying physical conditions that control ocean stratification and mixing. Although surface waves can be an important source of turbulent kinetic energy to the surface mixed layer, they have seldom been considered explicitly in studies of bloom formation. Here, we investigate the role of surface waves in bloom formation using a combination of satellite observations and numerical models. Satellite observations show a positive correlation between wave activity and chlorophyll concentration in the Northwest European shelf (May–September). In the deeper Northeast Atlantic, increased wave activity correlates with lower chlorophyll during periods of high phytoplankton activity (March-May) and higher chlorophyll when activity is low (below 54° N, July–September). We use a first-of-its-kind, km-scale, two-way coupled ocean-wave model system to investigate both the relationship between wave-driven mixing and bloom formation, and the sensitivity of model results to the method by which wave-driven mixing is parameterised. In deep regions, during the spring bloom, a wave-driven mixing event is likely to mix surface chlorophyll to deeper layers, away from light. In contrast, when phytoplankton activity is low in deep regions, wave-driven mixing can entrain nutrients, fueling the growth of nutrient starved phytoplankton near the surface. In June–October, in shallow but weakly stratified regions of the shelf, surface chlorophyll tends to be elevated following a wave-driven mixing event, which can bring to the surface both phytoplankton and nutrients from deeper layers. When contrasted with ocean-only runs, the two way-coupled ocean-wave model tends to produce greater vertical mixing and a delay in bloom onset. These results indicate bloom dynamics are sensitive to the way in which waves are modelled, and that the role of waves in bloom formation should be considered in future studies.

Therapeutic Drug Monitoring of Biologics: Current Practice, Challenges and Opportunities – a Workshop Report - Sophie Shubow; Michele Gunsior; Amy Rosenberg; Yow-Ming Wang; Tara Altepeter; Daphne Guinn; Mohsen Rajabiabhari; Joseph Kotarek; Diane R. Mould; Honghui Zhou; Adam S. Cheifetz; Sandra Garces; et al. (The AAPS Journal, 2025)

Impacts of a herring gull colony on runoff water quality from an urban green roof - Jinjie He; Elrod Owusu-Asumeng; Kate Zidar; Julian Stolper; Sudipti Attri; Jacob R. Price; Dustin Partridge; Franco Montalto; Christopher M. Sales (Science of The Total Environment, 2024)

Exploring reasons for high levels of food insecurity and low fruit and vegetable consumption among university students post-COVID-19 - Putu Novi Arfirsta Dharmayani; Miriam Williams; Carla Vanessa Alves Lopes; Rimante Ronto; Josephine Y. Chau; Stephanie R. Partridge; Seema Mihrshahi (Appetite, 2024)

Neuromorphic sensing of biomolecules covalently immobilised on polydimethyl glutarimide - Luke A. Sylvander; Phuong Y. Le; Hiep N. Tran; Billy J. Murdoch; Enyi Guo; David R. McKenzie; Dougal G. McCulloch; Jim G. Partridge (Analytica Chimica Acta, 2023)

Intra-catalyst CH4 oxidation pathways on a Pd/Al2O3/CeZrOx-based commercial catalyst and implications on NOx conversion profiles for a natural gas vehicle exhaust under lambda modulation - Dhruba J. Deka; Josh. A. Pihl; Calvin R. Thomas; William P. Partridge (Chemical Engineering Journal, 2023)

An experimental and computational analysis of combustion heat release transformation in dual fuel combustion - Kendyl R. Partridge; Prabhat R. Jha; Kalyan Kumar Srinivasan; Sundar Rajan Krishnan (Fuel, 2023)

Rock outcrops enhance abyssal benthic biodiversity - Alejandra Mejía-Saenz; Erik Simon-Lledó; Louis S. Partridge; Joana R. Xavier; Daniel O.B. Jones (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Liposome Click Membrane Permeability Assay for Identifying Permeable Peptides - Tanvi J. Desai; Bahanu Habulihaz; Joe R. Cannon; Arun Chandramohan; Hung Yi Kristal Kaan; Ahmad Sadruddin; Tsz Ying Yuen; Charles Johannes; Dawn Thean; Chris J. Brown; David P. Lane; Anthony W. Partridge; et al. (Pharmaceutical Research, 2021)

Correction to: Liposome Click Membrane Permeability Assay for Identifying Permeable Peptides - Tanvi J. Desai; Bahanu Habulihaz; Joseph R. Cannon; Arun Chandramohan; Hung Yi Kristal Kaan; Ahmad Sadruddin; Tsz Ying Yuen; Charles Johannes; Dawn Thean; Chris J. Brown; David P. Lane; Anthony W. Partridge; et al. (Pharmaceutical Research, 2021)

Letter to the Editor regarding Davis B, McDermott S, McCarter M, Ortaglia A. 2019. Population-based mortality data suggests remediation is modestly effective in two Montana Superfund counties. Environ. Geochem. Health - J. Griffin; B. Macgregor; N. Greene; C. R. Partridge; J. Bryson; R. A. Schoof (Environmental Geochemistry and Health, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Observations on the retina and ‘optical fold’ of a mesopelagic sabretooth fish, Evermanella balbo - H.-J. Wagner; J. C. Partridge; R. H. Douglas (Cell and Tissue Research, 2019)

Vamorolone, a dissociative steroidal compound, reduces collagen antibody-induced joint damage and inflammation when administered after disease onset - Jesse M. Damsker; Michaelyn R. Cornish; Priya Kanneboyina; Ila Kanneboyina; Qing Yu; Rachel Lipson; Aditi Phadke; Susan M. Knoblach; Karuna Panchapakesan; Melissa Morales; Alyson A. Fiorillo; Terence Partridge; et al. (Inflammation Research, 2019)

Toxicity of sediment pore water in Puget Sound (Washington, USA): a review of spatial status and temporal trends - Edward R. Long; R. Scott Carr; James M. Biedenbach; Sandra Weakland; Valerie Partridge; Margaret Dutch (Environmental Monitoring and Assessment, 2013)

Centromeric heterochromatin assembly in fission yeast—balancing transcription, RNA interference and chromatin modification - Benjamin J. Alper; Brandon R. Lowe; Janet F. Partridge (Chromosome Research, 2012)

Predicting possible negative impacts of weed biocontrol by artificially suppressing invasive hawkweed in New Zealand’s tussock grasslands - Pauline Syrett; Guy J. Forrester; Helen M. Harman; Colin D. Meurk; Trevor R. Partridge; Lindsay A. Smith (BioControl, 2012)

A comparison of the physiological consequences of head-loading and back-loading for African and European women - R. Lloyd; B. Parr; S. Davies; T. Partridge; C. Cooke (European Journal of Applied Physiology, 2010)

Direct and indirect effects of simulated calcareous dredge material on eggs and larvae of pink snapper Pagrus auratus - G. J. Partridge; R. J. Michael (Journal of Fish Biology, 2010)
The direct and indirect effects of a simulated, calcarenite‐based dredge material on eggs and larvae of pink snapper Pagrus auratus were assessed. Direct effects were assessed by measuring hatch rate or survival of eggs and pre‐feeding larvae, respectively, over a range of concentrations and exposure durations. Exposure of eggs to suspended solid concentrations up to 10 000 mg l −1 for 24 h did not affect egg buoyancy or hatch rate, despite sediment adherence occurring at the two highest concentrations tested. Newly hatched larvae, whose mouths were still closed, were relatively tolerant of suspended solids, with a 12 h lethal concentration resulting in 50% mortality, LC 50 , of 2020 mg l −1 and a first observable effect concentration of 150 mg l −1 . Once the larvae's mouths opened, tolerance was significantly reduced, with a 12 h LC 50 of 157 mg l −1 and a first observable effect concentration of 4 mg l −1 . Tolerance of larvae to suspended solids was negatively correlated with suspended solids concentration and exposure time, with exposure durations of ≤6 h being significantly less detrimental than those of 9 h or more. Indirect effects to larvae were assessed by measuring ingestion of copepod nauplii by 10 and 15 days post‐hatch (dph) larvae at sediment concentrations from 0 to 200 mg l −1 in 50 mg l −1 increments over 4 h. Ingestion was not significantly affected by sediment for 10 dph larvae, but by 15 dph, sediment had a far greater impact on ingestion, with larvae in all sediment treatments eating significantly fewer copepods than those in the control.

Factors affecting mark quality of alizarin complexone‐stained otoliths in juvenile black bream Acanthopagrus butcheri and a prescription for dosage - G. J. Partridge; G. I. Jenkins; R. G. Doupé; S. De Lestang; B. M. Ginbey; D. French (Journal of Fish Biology, 2009)
The relationships between otolith score, a function of increasing stain visibility, and the ratio of alizarin complexone (mg) to fish biomass (g) for 0·1, 0·6 and 7 g black bream Acanthopagrus butcheri show that acceptable marks are produced in all size classes using a stain‐to‐biomass ratio of 3·3 mg g −1 following an immersion period of 24 h.

Soil and vegetation responses to hydrological manipulation in a partially drained polje fen in New Zealand - B. K. Sorrell; T. R. Partridge; B. R. Clarkson; R. J. Jackson; C. Chagué-Goff; J. Ekanayake; J. Payne; P. Gerbeaux; N. P. J. Grainger (Wetlands Ecology and Management, 2007)

Deep sea benthic bioluminescence at artificial food falls, 1,000–4,800 m depth, in the Porcupine Seabight and Abyssal Plain, North East Atlantic Ocean - E. J. V. Gillibrand; P. Bagley; A. Jamieson; P. J. Herring; J. C. Partridge; M. A. Collins; R. Milne; I. G. Priede (Marine Biology, 2007)

Vision and visual variation in the peacock blenny - E. M. White; D. M. GonÇalves; J. C. Partridge; R. F. Oliveira (Journal of Fish Biology, 2004)
Microspectrophotometry (MSP) revealed the presence of a rod and at least two cone classes (mid‐ and long‐wavelength sensitive) in the intertidal peacock blenny Salaria pavo . Both rhodopsin and porphyropsin based visual pigments were found in all fish, together with high individual variation in the chromophore ratio. The three morphs (females, males and sneaker males) differed in their spectral sensitivities (as measured with the optomotor response) with sneakers having higher sensitivity at long‐wavelengths than either males or females. This long‐wave displacement of peak sensitivity could be due to elevated proportions of porphyropsin visual pigments in the sneakers’ retinae. The lenses of all morphs exhibited a short‐wavelength cut‐off and an unusual layer of carotenoid was found behind the retinal pigment epithelium and in the outer segments of some cones. These screening pigments could serve a photo‐protective role or to improve visual contrast. No short‐wave photoreceptors were located using MSP. This indicates that this cone class may be absent or present at very low numbers in the retina. This is the first in depth study of the visual system of a blenniid fish and indicates potential within‐species visual variation that may be related to the species’ habitat and morph‐specific behavioural requirements.

Pax7 distribution in human skeletal muscle biopsies and myogenic tissue cultures - Jens Reimann; Karima Brimah; Rolf Schrder; Anton Wernig; Jonathan R. Beauchamp; Terence A. Partridge (Cell and Tissue Research, 2004)

Mesoscale aspects of the Urban Heat Island around New York City - S. D. Gedzelman; S. Austin; R. Cermak; N. Stefano; S. Partridge; S. Quesenberry; D. A. Robinson (Theoretical and Applied Climatology, 2003)

Nitrogen and carbon isotope fractionation between mothers, neonates, and nursing offspring - Stacy G. Jenkins; Steven T. Partridge; Thomas R. Stephenson; Sean D. Farley; Charles T. Robbins (Oecologia, 2001)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

A late Holocene history of natural disturbance in lowland podocarp/hardwood forest, Hawke's Bay, New Zealand - Janet M. Wilmshurst; Matt S. McGlone; Trevor R. Partridge (New Zealand Journal of Botany, 1997)
Palaeoecological investigations of sediment cores from two lake basins in the Tutira and Putere districts of Hawke's Bay demonstrate the impact of volcanic activity, fires, and storms on the vegetation and soil stability before human settlement and deforestation. A “disturbance curve” derived from the classification and ordination of pollen records, and correlated with charcoal and sediment records, illustrates relative forest disturbance over time. Before anthropogenic forest clearance in Hawke's Bay, forest composition fluctuated frequently as a result of disturbance from fires, droughts, and a major volcanic eruption. Each natural disturbance, indicated by short‐term increases of seral taxa, was followed by complete forest redevelopment. Cyclonic storms were not a major cause of disturbance to lowland podocarp/hardwood forests in the region, nor to the bracken‐scrubland vegetation that replaced the forest after clearance. However, storms scoured and rapidly transported riverbank sediments into the lake basins. Compared with the preceding natural disturbances, deforestation by early Maori settlers represents a type and magnitude of disturbance previously unrecorded in the cores.

On the visual pigments of deep‐sea fish - R. H. Douglas; J. C. Partridge (Journal of Fish Biology, 1997)
The retinal visual pigments of 52 species of deep‐sea fish were measured by partial bleaching of detergent extracts. The retinae of 45 species contained only a single rhodopsin with maximum absorbance (λ max ) at a wavelength between 474 and 490 nm, matching both the region of highest intensity downwelling sunlight and the maximum emission of most deep‐sea bioluminescence. Seven species were shown to have more than one visual pigment within their retinae and these had λ max values that generally fell outside the usual range. One of these, Bonapartia pedaliota , was particularly interesting as, unlike most such multipigment species, it had one rhodopsin and one porphyropsin pigment, apparently based on different opsins. The relative proportions of the visual pigments in the seven multipigment species are presented.